1985
DOI: 10.1007/bf00051079
|View full text |Cite
|
Sign up to set email alerts
|

Determination of carbon balances for smog chamber terpene oxidation experiments using a 14C tracer technique

Abstract: In the last decade, numerous studies of monoterpene hydrocarbons in the presence of ozone and oxides of nitrogen have been completed. Although insights about the reactivity of terpenes have been gained, and several products have been identified in the gas and aerosol phases, carbon balances have been generally poor. This paper describes a radiotracer technique which accounts for carbon-containing compounds in a smog chamber at the conclusion of a photooxidation or ozonolysis reaction. Instead of attempting to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…A new pathway is proposed to explain their formation. According to Hooker et al [1985], the abstraction of a tertiary hydrogen atom of carbonyl products leads to peroxy radicals formation (ROO) as shown in Figure 11 (pathway P1, PAHD panel)…”
Section: 557mentioning
confidence: 99%
“…A new pathway is proposed to explain their formation. According to Hooker et al [1985], the abstraction of a tertiary hydrogen atom of carbonyl products leads to peroxy radicals formation (ROO) as shown in Figure 11 (pathway P1, PAHD panel)…”
Section: 557mentioning
confidence: 99%
“…NH~ NO 3 K* Na* Na" Na" Na ÷ ' Na* from Dehnas and Servant (19821 hypothesized that some of them may rapidly undergo oxidation close to the source (Hooker et al, 1985); this is suggested by the physical data presented above. Important CO mixing ratios obtained in these regions indicate also a fast decomposition of numerous organic species (Zimmerman et al, 1978;Logan et al, 1981;Crutzen et al, 1985).…”
Section: Chemical Composition Of the Aerosolmentioning
confidence: 88%
“…In the monoterpene plume from conifer processing, nitrogen oxides required for efficient ozone formation are provided by the diesel engine. The ozonolysis of the monoterpenes also gives rise to immediate formation of radicals, aldehydes, peroxides and other potentially harmful photo-oxidants (Hooker et al, 1985;Gäbetal., 1985).…”
Section: Photo-oxidant Aspectsmentioning
confidence: 99%